2012
DOI: 10.1089/jwh.2011.3254
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Adjuvant Hormonal Therapy Use

Abstract: Background: In the United States, 5-year breast cancer survival is highest among Asian American women, followed by non-Hispanic white, Hispanic, and African American women. Breast cancer treatment disparities may play a role. We examined racial/ethnic differences in adjuvant hormonal therapy use among women aged 18-64 years, diagnosed with hormone receptor-positive breast cancer, using data collected by the Northern California Breast Cancer Family Registry (NC-BCFR), and explored changes in use over time. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…Specifically, study suggests that African-Americans are primarily and persistently at higher risk of death only for HR+/HER2- breast cancers at Stages II and III, for which breast cancers respond favorably to anti-endocrine therapy or trastuzumab therapy (37). This underscores the central role of treatment in the black/white disparity in breast cancer, even though no race/ethnicity differences in adjuvant hormone therapy use were identified in two recent studies (38, 39). Unfortunately, information on endocrine therapies is under-captured in cancer registry data, and specific information regarding receipt of trastuzumab is not reported.…”
Section: Discussionmentioning
confidence: 73%
“…Specifically, study suggests that African-Americans are primarily and persistently at higher risk of death only for HR+/HER2- breast cancers at Stages II and III, for which breast cancers respond favorably to anti-endocrine therapy or trastuzumab therapy (37). This underscores the central role of treatment in the black/white disparity in breast cancer, even though no race/ethnicity differences in adjuvant hormone therapy use were identified in two recent studies (38, 39). Unfortunately, information on endocrine therapies is under-captured in cancer registry data, and specific information regarding receipt of trastuzumab is not reported.…”
Section: Discussionmentioning
confidence: 73%
“…84 This same study demonstrated that racial/ethnic differences in ET use decreased as the diffusion of ET into clinical practice increased over time. 84 …”
Section: Resultsmentioning
confidence: 85%
“…Eight studies 19,22,60,79,82,83,85,87 used large secondary data sources or medical records to examine racial/ethnic and socioeconomic disparities in ET use; of these, 3 77,79,86 examined adjuvant breast cancer therapy broadly, including not only ET use but also either chemotherapy, or chemotherapy with radiation therapy. Although these studies evaluated chemotherapy and radiation therapy as dependent variables, some studies included these treatment variables (i.e., surgery, chemotherapy, radiation) as predictor variables of ET use 19,22,60,81,82,84,87 and other studies 78,80,83 , did not include treatment variables in their analyses. One study stratified results by chemotherapy receipt.…”
Section: Resultsmentioning
confidence: 99%
“…Demographics, healthcare factors, patient-provider communication, and social support have been associated with AHT adherence (e.g. Livaudais et al, 2012; Murphy, Bartholomew, Carpentier, Bluethmann, & Vernon, 2012). As social support is expanded online, breast cancer survivors are more likely to seek support on OSGs (Davison, Pennebaker, & Dickerson, 2000).…”
Section: Tamoxifenmentioning
confidence: 99%